Pengetahuan Gizi dan Keaktifan Ibu Balita dalam Kunjungan Posyandu Berhubungan dengan Status Gizi Balita - Wahyu Elia Ramadani; Afriyana Siregar; Desri Suryani (Jurnal Ilmu dan Teknologi Kesehatan, 2019)
Children nutritional problem in Indonesia remains as a challenge in health aspect. Several ways that can affect children nutrient status namely; the mothers’ knowledge towards nutrition and their activeness in Posyandu. In order to achieve the optimal status of children nutrition, the mothers need to be involved in Posyandu activity so the nutritional status can be monitored. This research aimed to discover the relation between nutrition knowledge and mother’s activeness in Posyandu visitation with children nutritional status in Puskesmas Pasar Ikan working area, Bengkulu, in 2019. This research used observational method and cross sectional approach. The technique that was used is quota sampling technique with 92 repondents. Chi square was used as statistic analysis tool. This research showed that 43,5% of children nutrition in normal status, 2,2% in critical status, and the last 54,3% in chronic status. The majority of sample showed a sufficient knowledge about nutrition with 40,2%. The active respondent with more that 8 visits showed a satisfying numbers with 68,5%, meanwhile the other only acquired 31,5%. The result of chi square statistic showed that there was a connection between knowledge about nutrition and mothers’ activeness in Posyandu visitation with children nutritional status.